Pengaruh Pemberian Insentif Terhadap Prestasi Kerja Karyawan Pada PT Wahyu Promo Citra Jakarta - Nurlaela Eva puji Lestari (Cakrawala - Jurnal Humaniora, 2019)
Human resource management can also produce a good performance in a company by assessing, giving rewards for each individual member of the organization or company in accordance with their respective work capabilities. The human resources department that designs and administers incentive policies as one part of compensation. If a company is able to provide incentives precisely and precisely, it will be one of the most appropriate ways for employees to improve their work performance. Samples used for collection the data in this research are 44 employees at PT Wahyu Promo Citra Jakarta. The purpose of this study is to find out and analyze the relationship between Giving Incentives (X) on Employee Performance (Y) at PT Wahyu Promo Citra Jakarta. Based on the analysis and processing of data based on the calculation of the correlation coefficient, it can be seen that Giving Incentives has a strong relationship that is equal to 0.664 and according to the calculation results the coefficient of determination can be known which is 44.1%, so the relationship between Giving Incentives (X) and Employee Performance (Y) it can be concluded that there is a strong relationship.